Review of species of the Old World genus Doryctophasmus Enderlein, 1912 (Hymenoptera: Braconidae: Doryctinae) - Belokobylskij, Sergey A. (Zootaxa, 2015)
The Old World doryctine wasp genus Doryctophasmus Enderlein, 1912 is reviewed. Two new species, D. beninus sp. nov. and D. madagascarus sp. nov., are described and illustrated from the Afrotropical region. The illustrated redescriptions of D. ferrugineiceps Enderlein, 1912, D. ferrugineus (Granger, 1949) and D. rubrotestaceus (Granger, 1949) are provided. Lectotypes of Doryctes ferrugineus Granger 1949 and D. rubrotestaceus Granger 1949 are designated. A key for determination of six know species of Doryctophasmus is given.